PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pelanggan Larissa Aesthetic Center Semarang) - Wahyudien, Ifrina Kurniasari; Widiartanto, Widiartanto; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
The research was motivated by the increasing number of beauty clinics which offer various kinds of products and treatments to meet the needs of community in the field of beauty. Larissa Aesthetic Center Semarang is one of the beauty clinic that seeks to meet the needs of consumers in the field of beauty care with the concept using natural ingredients. Customer visits in Larissa Aesthetic Center Semarang each year has not reached the target. It indicates a problem with Larissa’s customer loyalty.The purpose of this research is to find out the influence of product quality and service quality toward customer loyalty through customer satisfaction as an intervening variable. The type of this research is explanatory research. The population is all of Larissa Aesthetic Center Semarang customers. While the sample of this study are 100 customers. Data collection is using a questionnaire with purposive sampling. The analytical method used in this study is two-stage regression analysis using the software SPSS for Windows version 17.0, where the validity test, reliability test, coefficient of correlationt, simple and multiple regression, the determination coefficient, significance test (t test and F test) are done first. Based on two-stage regression analysis results show that variable product quality (X1) and service quality (X2), whether partially or simultaneously have a positive and significant toward customer satisfaction (Z). Partially, variable customer satisfaction (Z) also has a positive and significant toward customer loyalty (Y). Based on the research results, the company is expected to improving customer satisfaction and customer loyalty by maintain the quality of products and quality of services provided. Larissa had to control all the composition of the ingredients used in the manufacture of each product. In addition, Larissa should hold routine evaluation for employees in providing treatment to make employees more skilled in providing outstanding service. It is also a good idea that Larissa can add the variety of products and treatment in order to increase the completeness type of beauty treatment in Larissa.